Sustainable Space Management in the Coastal Area of Medan Belawan - M. Almuttaqin; Abdi Sugiarto; Cut Nuraini (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Sustainable management of coastal spaces is a major challenge in urban-coastal planning, especially in vulnerable areas such as Medan Belawan. This study aims to identify and analyze the influence of six independent variables on the sustainability of coastal space management. The variables studied included Microecological Inequality, Inclusivity of Coastal Asset Ownership, Adaptive Preparedness to Climate Risks, Inter-Functional Spatial Connectivity, Local Institutional Accountability, and Communal Social Resilience. The method used is a quantitative approach with a multiple linear regression model on primary data obtained through surveys, field observations, and in-depth interviews with 150 respondents.The results showed that five of the six variables had a significant effect on the sustainability of coastal space management. The most dominant variable was Local Institutional Accountability, followed by Asset Inclusivity, Ecological Inequality, Social Resilience, and Adaptive Readiness. Meanwhile, Connectivity between Spatial Functions does not have a significant impact. The regression model shows an R² value of 0.539 which means that 53.9% of the variation in coastal space management can be explained by these six variables.These findings imply the importance of strengthening participatory governance, equitable distribution of space access, and building community's adaptive capacity as a cornerstone for contextual and sustainable coastal spatial planning. Strategic recommendations are directed at institutional reform, community-based planning, and micro-ecological conservation in urban-coastal areas.